2016
DOI: 10.3847/0004-637x/819/1/77
|View full text |Cite
|
Sign up to set email alerts
|

Globular Clusters and Spur Clusters in NGC 4921, the Brightest Spiral Galaxy in the Coma Cluster

Abstract: We resolve a significant fraction of globular clusters (GCs) in NGC 4921, the brightest spiral galaxy in the Coma cluster. We also find a number of extended bright star clusters (star complexes) in the spur region of the arms. The latter are much brighter and bluer than those in the normal star-forming region, being as massive as 3×105 M e . The color distribution of the GCs in this galaxy is found to be bimodal. The turnover magnitudes of the luminosity functions of the blue (metal-poor) GCs (0.70<(V − I)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 59 publications
6
19
0
Order By: Relevance
“…5 with a Sérsic law (Sérsic 1963), we obtain the Sérsic index values, n AGC = 1.41 ± 0.34 for all globular clusters, n BGC = 1.07±0.28 for the blue globular clusters, and n RGC = 1.89±0.83 for the red globular clusters. These values are similar to those of NGC 4921 (Lee & Jang 2016). The corresponding effective radii of the globular cluster systems are R eff,AGC = 0.…”
Section: Radial Distributions Of the Globular Clusterssupporting
confidence: 79%
See 2 more Smart Citations
“…5 with a Sérsic law (Sérsic 1963), we obtain the Sérsic index values, n AGC = 1.41 ± 0.34 for all globular clusters, n BGC = 1.07±0.28 for the blue globular clusters, and n RGC = 1.89±0.83 for the red globular clusters. These values are similar to those of NGC 4921 (Lee & Jang 2016). The corresponding effective radii of the globular cluster systems are R eff,AGC = 0.…”
Section: Radial Distributions Of the Globular Clusterssupporting
confidence: 79%
“…We derived F 814W aperture correction values for the sources including star cluster candidates following the method as used in Lee & Jang (2016). The steps are as follows.…”
Section: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the distance of the Coma cluster ( -» m M 35), a GC system with a standard Gaussian luminosity function for a low-mass earlytype galaxy (with mean M V = −7.3 mag; Miller & Lotz 2007) has a peak whose measurement is within the reach of these observations (V 0 ≈ 27.7 mag). Lee & Jang (2016) showed that GCLF distances to the Coma cluster can be obtained with HST imaging. For this analysis, we use our "deep" sample, which extends to V 606 = 29 mag.…”
Section: The Gc Luminosity Function and The Distance To Df17mentioning
confidence: 99%
“…In the CDF, two modes (MP and MR) are clearly present, and the MP mode is much more dominant for the IGC. Color-magnitude diagrams for the GC populations around both NGC 4874 and 4889 from HST ACS imaging are presented and briefly discussed by Lee & Jang (2016a), while Cho et al (2016) complete a more comprehensive discussion specifically for the NGC 4874 system, now including threecolor ( ) g I H , , photometry. A structural feature held in common by all four of the Galaxy clusters discussed here (Coma, A2052, A2147, and A2199 from Paper II) is a prominent X-ray halo gas component.…”
Section: Metallicity and Color Distributionsmentioning
confidence: 99%